Methodological Aspects of the Theory of Objectification - Radford, Luis (Perspectivas da Educação Matemática, 2015)
In this article, I focus on the methodology of a specific theory of teaching and learning: the theory of objectification. Inspired by dialectical materialism and Vygotsky’s psychology, the theory of objectification posits the goal of Mathematics Education as a dynamic political, societal, historical, and cultural endeavour aimed at the dialectical creation of reflexive and ethical subjects who critically position themselves in historically and culturally constituted and always evolving mathematical discourses and practices. In the first part, I briefly sketch the general lines of the theory. In the second part, emphasizing the semiotic and embodied nature of teaching and learning, I discuss the methodology of the theory, stressing in particular its task design, data collection, and data analysis components.